La prohibición de asistencia financiera en las sociedades de capital: su incumplimiento a la luz de la actual jurisprudencia en España - de Vivero de Porras, Carmen (2024)
The prohibition of financial assistance by capital companies to a third party to acquire its own shares or participations (as well as those of another group or parent company) contained in articles 143.2 and 150.1 both of the LSC, has given rise to very diverse judgments. The number of cases that we face on a daily basis is diverse and plural, so that on several occasions it is difficult to adequately protect the interests at stake in view of the businesses that may be affected by the prohibited assistance. In recent years, a restrictive interpretation of nullity has been imposed by the Supreme Court in Spain, as well as once declared null and void whether it can or should affect other businesses and even the acquisition itself, which the Supreme Court denies. This paper analyzes the doctrine of the High Court and the extension or not of the nullity of the prohibited assistance to the business of acquisition of own shares or participations, starting from the patrimonial or financial purpose (on which the High Court is based) and/or the control regime that such assistance may grant in the company to the person who obtains it.